2019
DOI: 10.1055/s-0039-1688692
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with General versus Local Anesthesia during Carotid Endarterectomy

Abstract: Background and Study Aims Both general and local anesthesia are used in our department for carotid endarterectomy (CEA). The decision as to which anesthetic technique to use during surgery is made individually. The aim of our study was to evaluate patient satisfaction and preference with the anesthesia type used. Material and Methods The satisfaction of a group of 205 patients with regard to anesthesia used and their future preferences were evaluated prospectively through a questionnaire. The reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In addition, it is known that the patient satisfaction is higher than regional anesthesia in patients who underwent CEA under general anesthesia. [22] Our study, in which both groups were under general anesthesia, revealed that the addition of ICPB further increased patient satisfaction. This study has some limitations.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In addition, it is known that the patient satisfaction is higher than regional anesthesia in patients who underwent CEA under general anesthesia. [22] Our study, in which both groups were under general anesthesia, revealed that the addition of ICPB further increased patient satisfaction. This study has some limitations.…”
Section: Discussionmentioning
confidence: 65%
“…[4] In addition, general anesthesia may be somewhat advantageous in terms of patient satisfaction. [5] On the other hand, cervical plexus blocks may provide effective postoperative analgesia and stable hemodynamics. [6] However, in almost all of these comparisons, analgesia was provided with oral and/or intravenous medications in the general anesthesia groups.…”
Section: Introductionmentioning
confidence: 99%
“…In the comparison of general anesthesia and regional anesthesia, patients feel less pain and higher satisfaction with general anesthesia. 6 In our clinical approach, general anesthesia is our primary option for both to increase surgical comfort and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery might be performed under local or general anesthesia, and arteriotomy might be repaired by patchplasty or primary sutures. [2][3][4][5][6] There is still no consensus in these practical approaches, which could change according to the specialist's experiences and available conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with this theoretical review the authors showed that the factors that determine satisfaction are several and diverse and include aspects related to the patient, the anesthesiology staff, the surgery and the health institution. Another finding of this review is that various instruments are used to measure patient satisfaction with anesthesia, some of these have been widely validated 8,12,13,16,18,21-23,25,28, while others are less robust and were created only to analyze a specific case series 3,9,17,19,20,24,26. These variations could be the explanation for the notable differences between the satisfaction reports observed in this research.…”
Section: Discussionmentioning
confidence: 99%